An Investigation into Modelling Solids Friction for Dense Phase Pneumatic Conveying System - Kumar, Deepak (My University, 2014)
This report presents the ongoing investigation for pressure drop in pipe for fluidized dense phase pneumatic conveying system of powders and granular particles. This thesis report includes the modeling of solid friction factor for straight pipes. The modeling is done on the basis of previous researches by considering the solid friction factor depends upon certain parameters, and these parameters are here modified with keeping in mind that the solid friction factor will remain dimensionless. The work is carried out by collecting data for pressure drop for 20different materials conveyed through different pipe configurations. The whole data is compiled at one place and an attempt is made to model a general solid friction factor which will work on any bulk material and on any pipe configuration used for dense or dilute phase pneumatic conveying system. The model so developed gives good predictions when compared with Pan (1992) data for pressure drop in total pipeline for Fly ash (particle density 2197 kg/m3) and pulverized brown coal (particle density 1488 kg/m3) in six different pipe configurations, but somehow gives very alarming results when it is done with the experimental data obtained at Thapar University, Patiala laboratory using Fly ash (particle density 1950 kg/m3, median particle diameter 45m) in three different pipe configurations.
ME, MED
Keywords: solids friction; pneumatic conveying; pressure drop; powders